Analysis of Free Cash Flows of Joint Stock Companies In Uzbekistan - Foziljanov I.S., (European Journal of Life Safety and Stability (2660-9630), 2022)
The article describes the analysis of the state of free cash flows of joint-stock companies. Also, the financial indicators of the joint-stock companies were analyzed. In particular, free cash flows from joint-stock companies in our country were calculated based on the data of JSC "Andijondonmahsulot" and the amount of cash flows was determined.